Groups, networks, and social capital in the Philippine communities - Godquin, Marie; Quisumbing, Agnes R. (International Food Policy Research Institute, 2006)
This paper explores the determinants of group membership and social networks of rural households using a unique longitudinal data set from the rural Philippines. We investigate two types of social capital: membership in groups (production, credit, burial, religious and civic groups), or “formal” social capital, and size of trust-based networks or “informal” social capital. Because men and women may have different propensities to invest in social capital, we analyze the determinants of group membership both at the household level and for men and women separately. We also disaggregate the analysis by type of group. The paper examines the determinants of the density of social capital, proxied by the number of groups and the number of network members. Finally, it explores various reasons why people might join groups—whether groups increase trust, or whether groups increase well-being, as proxied by per capita expenditure. We find that asset-rich, better-educated households and households living closer to town centers are more likely to participate in groups and to have larger social and economic assistance networks. Different aspects of village-level heterogeneity have different impacts on group membership, and greater exposure to shocks and a higher incidence of peace and order problems increase group membership. Men and women do not differ significantly in the number of groups they join, however, there are clear gender differences in the types of groups to which men and women belong. We also find that group membership does not, in general, increase network density and we do not find evidence of positive returns to group membership in terms of increased per capita expenditures.